1996
DOI: 10.1139/o96-002
|View full text |Cite
|
Sign up to set email alerts
|

Characterization, chromosomal mapping, and expression of different ubiquitin fusion protein genes in tissues from control and heat-shocked maize seedlings

Abstract: Organisms possess at least two multigene families of ubiquitins: the polyubiquitins, with few to several repeat units, which encode a ubiquitin monomer, and the ubiquitin fusion (or extension) protein genes, which encode a single ubiquitin monomer and a specific protein. This report provides details about two ubiquitin fusion protein genes in maize referred to as MubG7 (uwo 1) and MubG10 (uwo 2). Each has one nearly identical ubiquitin coding unit fused without an intervening nucleotide to an unrelated, 237-nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…). Previous studies have identified some ubiquitin extension protein genes, which encode either one of two different ribosomal subunits in the C‐terminus of ubiquitin domain (Liu et al , Shaheen et al ). In this study, four G. soja ubiquitin genes and four Arabidopsis ubiquitin extension protein genes were clustered in clade C (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…). Previous studies have identified some ubiquitin extension protein genes, which encode either one of two different ribosomal subunits in the C‐terminus of ubiquitin domain (Liu et al , Shaheen et al ). In this study, four G. soja ubiquitin genes and four Arabidopsis ubiquitin extension protein genes were clustered in clade C (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies reported that these three groups of genes play an important role in response to abiotic stresses. For example, the ubiquitin‐like gene HUB1 confers drought tolerance in perennial ryegrass (Patel et al ) and the ubiquitin extension genes play an important role in response to heat‐shock (Liu et al , Park et al ). However, most studies focus on the ubiquitin‐proteasome system, which has been widely reported to have multiple functional roles in regulating plant stress responses (Hwang et al , Sharma et al ).…”
Section: Introductionmentioning
confidence: 99%
“…In Arabidopsis UBQ14 levels increased in parallel with the induction of HSP70, while UBQ11 decreased (Sun & Callis, 1997). Specific ubiquitin alleles were also shown to be upregulated in specific organs after heat stress in maize (Liu et al, 1996), and a ubiquitin-conjugating enzyme has been shown to be upregulated by heat shock in tomato plants (Feussner et al, 1997). Similarly, ubiquitin pathway genes showed increased transcript levels in heat-stressed tobacco (Rizhsky et al, 2002).…”
Section: Other Heat-stress Regulated Genesmentioning
confidence: 96%